1956
DOI: 10.1111/j.1365-2621.1956.tb16966.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ABSORBABILITY OF NATURAL AND MODIFIED FATSa

Abstract: IZTZ with the technical assistance of JOHN J. McMULLEN AND LUCIUS V. THOMAS Qitartermaste~ Food and Container InstittLte for the iZr?iieti Forces Chicago, IllinoisMost natural fats have been shown to be readily digested, but in the case of naturally-occurring fats of high melting point and of fats hardened by hydrogenation, the coefficient of digestibility may be reduced. Two major theories have been propounded to explain differences in digestibility :(1) that digestibility is inversely proportional to and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1959
1959
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Fat absorption was 99.6% with FctO consumption, which is similar to that observed in an animal trial comparing the digestibility of different types of fat (36). Also, earlier studies of the absorbability of fats in rats showed that coconut oil, which is rich in MCT, is 99.7% absorbed (37). With OL consumption, fat absorption was measured to be 99.7%, which is greater than the 97.4% absorption rate reported by Jones et al (38) for oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Fat absorption was 99.6% with FctO consumption, which is similar to that observed in an animal trial comparing the digestibility of different types of fat (36). Also, earlier studies of the absorbability of fats in rats showed that coconut oil, which is rich in MCT, is 99.7% absorbed (37). With OL consumption, fat absorption was measured to be 99.7%, which is greater than the 97.4% absorption rate reported by Jones et al (38) for oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of non-ruminant animals it has been established that the extent to which a fat is absorbed is influenced by the proportions and chain length of the saturated fatty acids (Calloway et al 1956), the degree of unsaturation of the fat (Young & Garrett, 1963) and the arrangement of the fatty acids within the glyceride molecules (Renner & Hill, 1961;Mattson & Volpenheim, 1962;Davis, 1965). These observations have contributed to the current situation in which it is normal practice to include fats in rations designed for various classes of poultry, and to a lesser extent pigs.…”
Section: Discussionmentioning
confidence: 98%
“…studies; (6)Bayley (1963); (c)Benner & Hill (1961); (d)Lewis & Payne (1966); (e)Young (1961); (/)Hoagland & Snider (1943); {g)Fedde, Waibel & Burger (1960); (ft)Peterson & Vik-Mo (1968); (i)Calloway et al (1956); (j)March & Biely (1957).…”
mentioning
confidence: 98%
“…Earlier studies of the absorbability of fats in rats showed that coconut oil is 99.7% absorbed compared to 98% for lard. 32 If we consider that RMR accounts for approximately 8 h daily and that the remaining time is spent in the post-meal period, then the average difference in EE with MCT consumption compared to LCT, as measured by indirect calorimetry, can be extrapolated to be 40.2 kcal on day 2 and 50.2 kcal on day 27. This would translate into a 0.14 -0.18 kg weight loss over a 27 day period.…”
Section: Discussionmentioning
confidence: 99%